2019
DOI: 10.1016/j.mito.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of air pollution on mitochondrial function, mitochondrial DNA methylation, and mitochondrial peptide expression

Abstract: Mitochondrial DNA is sensitive to damage by exogenous reactive oxygen sources, including traffic-related air pollution (TRAP). Given the important role for mitochondria in human disease, we hypothesized that prenatal air pollution exposure may be associated with mitochondrial dysfunction and that mitochondrial-derived peptides (MDPs) might protect against these effects. In in vitro studies, 24-hour exposure to nanoparticulate matter (nPM) increased oxidation of mtDNA, decreased mitochondrial consumption rate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 63 publications
(60 reference statements)
2
47
0
Order By: Relevance
“…MtDNAcn can be used as another indicator of mitochondrial damage because it correlates with the size and number of mitochondria in a cell and may change under different cellular energy demands or different physiological or environmental conditions [33,54]. Recent studies have correlated ambient PM exposure with mitochondrial DNA damage [26,33,54]. Similar to our study, a previous study found that personal exposure to fine PM and benzo [a] pyrene from indoor air pollution reduced MtDNAcns in leukocytes of women from China [55].…”
Section: Early Apoptotic Cells Can Become Late Apoptotic Cells If Thesupporting
confidence: 86%
See 2 more Smart Citations
“…MtDNAcn can be used as another indicator of mitochondrial damage because it correlates with the size and number of mitochondria in a cell and may change under different cellular energy demands or different physiological or environmental conditions [33,54]. Recent studies have correlated ambient PM exposure with mitochondrial DNA damage [26,33,54]. Similar to our study, a previous study found that personal exposure to fine PM and benzo [a] pyrene from indoor air pollution reduced MtDNAcns in leukocytes of women from China [55].…”
Section: Early Apoptotic Cells Can Become Late Apoptotic Cells If Thesupporting
confidence: 86%
“…Mitochondria are the major cellular sources of ROS, which are generated as byproducts during normal respiration [26,29,54]. The alterations in ROS levels, the structural changes in the mitochondria observed using TEM and even the reductions in SOD2 levels may suggest that exposure to water-soluble wood tar can lead to mitochondrial damage.…”
Section: Early Apoptotic Cells Can Become Late Apoptotic Cells If Thementioning
confidence: 99%
See 1 more Smart Citation
“…However, the field remains at a nascent stage, with little understanding of the mechanisms underpinning how mtDNA methylation levels may be implicated in the etiology of CVD and/or platelet activation. Recently, it has been demonstrated that mtDNA methylation regulates expression of mitochondrial-derived peptides (MDP) with cytoprotective function [38] suggesting that mtDNA methylation level may be indicative of the overall stress to which the cell is exposed. Additionally, in vitro studies have shown that the presence of 5methylcytosine can alter mitochondrial transcription factor (TFAM) binding and transcription initiation [39].…”
Section: Discussionmentioning
confidence: 99%
“…It is not known whether these small changes in DNA methylation reflect changes in gene expression. Regardless, they may serve as a biomarker of a cascade of other biological reactions [43][44][45], such as MDP regulation [38].…”
Section: Discussionmentioning
confidence: 99%